Photojournalism and genre stereotypes: Case of Study: World Press Photo - Irala, Pilar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Photojournalism is not free from stereotypical representations. The fourth power still maintains inertias regarding the presentation and representation of stereotypes related to women. The main objective of this research is to explain this circumstance, give examples and provide solutions so that photojournalism can be an effective tool in the dissemination of alternative images. To this end, the bibliography on journalism and gender will be reviewed, as well as stereotypes in the press and, especially, in visual representation. In addition, the last few years of the World Press Photo Awards will be analysed to compare the results with the hypothesis put forward.